Probabilistic language of prospective childhood education teachers (Edma 0-6: Educación Matemática en la Infancia, 2024)
The aim of this paper was to assess the language of chance and the qualitative graduation of probabilities of 132 pre-service early childhood teachers. To do so, their answers to a questionnaire with items taken from previous research with secondary school students were analysed. Although the results obtained are better than those of previous research, part of the sample was unable to give correct synonyms for some probabilistic terms, had difficulty with the expressions "impossible" and "50% probability" and made inadequate assessments of probability in weather forecasting.
Keywords: Probability; Intuitive approach; Language; Prospective teachers; Childhood education